Trace metal data from water column samples during RV Maria S. Merian cruise MSM80 off the northern Humboldt Upwelling System - Leila Kittu; Mark James Hopwood; Allanah Joy Paul; Mar Fernández-Méndez; Eric Pieter Achterberg; Ulf Riebesell (PANGAEA, 2021)
This data is part of the BMBF projects CUSCO (Coastal Upwelling Systems in a Changing Ocean) and BioTip subproject Humboldt Tipping. The file contains total dissolvable trace metal concentrations (Fe, Cd, Ni, Cu, Zn and Co) from various depths of sampled stations. Trace metal concentrations were determined via Inductively coupled plasma mass spectrometry (ICP-MS, Element XR, ThermoFisher Scientific) after pre-concentration as per Rapp et al. (2017).